1990
DOI: 10.1056/nejm199006213222504
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak of Toxic Encephalopathy Caused by Eating Mussels Contaminated with Domoic Acid

Abstract: In Canada in late 1987 there was an outbreak of an acute illness characterized by gastrointestinal symptoms and unusual neurologic abnormalities among persons who had eaten cultivated mussels. Health departments in Canada solicited reports of this newly recognized illness. A case was defined as the occurrence of gastrointestinal symptoms within 24 hours or of neurologic symptoms within 48 hours of the ingestion of mussels. From the more than 250 reports received, 107 patients met the case definition. The most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
364
2
5

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 684 publications
(380 citation statements)
references
References 17 publications
5
364
2
5
Order By: Relevance
“…1,5,6,8,21,22 Of direct relevance to development of our hypothesis were indications that systemic dosing with domoic and kainic acids provoke the formation of epileptiform activity originating primarily from the hippocampus. 49 Using intrahippocampal dosed animals, Sawant and colleagues 13 from our research group used electrocorticography to show that DOM-induced epileptiform discharges spread rapidly to surrounding extralimbic regions.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…1,5,6,8,21,22 Of direct relevance to development of our hypothesis were indications that systemic dosing with domoic and kainic acids provoke the formation of epileptiform activity originating primarily from the hippocampus. 49 Using intrahippocampal dosed animals, Sawant and colleagues 13 from our research group used electrocorticography to show that DOM-induced epileptiform discharges spread rapidly to surrounding extralimbic regions.…”
Section: Discussionmentioning
confidence: 89%
“…3,4 Clinical reports of neurological symptoms including seizures, amnesia, and coma coupled with postmortem evidence of hippocampal and amygdaloid nucleus necrosis and astrocytosis were particularly noted among severe cases of DOM ingestion. 1,5,6 Among these cases, the authors also reported cardiovascular disturbances, including cardiac arrhythmias and hypotension. 1 As a consequence of heightened interest in the mechanism of DOM toxicity, a number of experimental studies have investigated the consequences of DOM exposure on behavioral and neurological responses in laboratory animals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…DA gained notoriety as the causative agent of amnesic shellfish poisoning in 1987, when human consumption of contaminated mussels led to illness and deaths. 19 DA may also pose a risk to marine wildlife and has caused mass mortalities of seabirds 25,37 and marine mammals. 23 Initially described as the antihelmintic component of ''domoi,'' a Japanese folk medicine derived from the red algae Chondria armata, 28 DA is a potent agonist of the alpha-amino-3-hydroxyl-5-methyl-4-isoxazole propionate (AMPA) and kainate subclasses of the neuronal glutamate ionotropic receptors.…”
Section: Pathology Of Domoic Acid Toxicity In California Sea Lions (Zmentioning
confidence: 99%
“…DA produced during a HAB may undergo trophic transfer by accumulating in algivorous or filter-feeding species such as anchovy, 13 Dungeness crab, razor clam, 36 or mussels. 19 Other algal toxins of concern in US waters include saxitoxin, brevetoxin, okadaic acid, ciguatoxin, and Pfeisteria-associated toxin. DA gained notoriety as the causative agent of amnesic shellfish poisoning in 1987, when human consumption of contaminated mussels led to illness and deaths.…”
mentioning
confidence: 99%